Del Paleoindio al formativo: 10.000 años para la historia de la tecnología lítica en Colombia (2012)
ABSTRACT: This paper provides an overview of the lithic technology of human groups that inhabited Colombian territory since the Late Pleistocene through middle Holocene. The aim is to review the evolution of lithic technology analysis, from the three earliest periods: Paleoindian, Archaic, and Formative, in different regions of the country.